Coupling Canonical Boundary Element Method with FEM to Solve Harmonic Problem over Cracked Domain (Journal of Computational Mathematics, 1983)
Using the canonical boundary reduction, suggested by Feng Kang, coupled with the finite element method, this paper gives the numerical solutions of the harmonic boundary-value problem over the domain with crack or concave angle. When the coupling is conforming, convergence and error estimates are obtained. This coupling removes the limitation of the canonical boundary reduction to some typical domains, and avoids the shortcoming of the classical finite element method, because of which the accuracy is damaged seriously and the approximate solution does not reflect the behaviour of the solution near the singularity. Numerical calculations have verified those conclusions.